Analisis Pengaruh Parameter Pemotongan terhadap Kekasaran Permukaan pada Proses Turning Baja AISI 1045 - Aldy Rachman; Ahmad Maulana; ⁠Dani Irawan (Pusat riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of cutting parameters on surface roughness in the turning process of AISI 1045 steel. The investigated parameters include cutting speed, feed rate, and depth of cut. A quantitative approach was employed using multiple linear regression analysis with SPSS software. The dataset consisted of 30 simulated experimental observations with varying cutting parameter conditions. Prior to regression analysis, classical assumption tests including normality, multicollinearity, and heteroscedasticity tests were conducted to ensure the validity of the model. The results indicated that all assumptions were satisfied. The findings reveal that simultaneously, all independent variables have a significant effect on surface roughness with a coefficient of determination of 82.1%. Partially, Feed rate and cutting speed significantly influence surface roughness, while depth of cut does not show a significant effect. Feed rate is identified as the most dominant variable affecting surface roughness, where an increase in Feed rate leads to higher roughness values. In contrast, increasing cutting speed tends to reduce surface roughness. This study highlights the importance of controlling cutting parameters, particularly Feed rate and cutting speed, to improve machining quality. The results provide practical implications for manufacturing industries in optimizing machining parameters to achieve better surface quality and process efficiency.